2016
DOI: 10.1016/j.joms.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Immediate Allograft Reconstruction of Long-Span Defects of the Inferior Alveolar Nerve

Abstract: Immediate reconstruction of the IAN with allogeneic nerve grafting of long-span defects (≥5 cm) is a viable and predictable option to achieve useful functional sensory recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 19 publications
3
50
0
5
Order By: Relevance
“…8 In addition, the most appropriate time to consider nerve grafting is at the time of resection and reconstruction because a delayed approach would allow time for wallerian degeneration of the resected nerve stumps, possible trigeminal ganglion cell body death, 9 and the MILORO AND MARKIEWICZ possibility of central cortical changes that would affect the success of microneurosurgical repair. Our preliminary data have been published, 5 and the results of neurosensory recovery using VSP appear to be consistent with those results; however, additional investigation is required to determine whether an improved outcome in sensation can be observed with VSP.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…8 In addition, the most appropriate time to consider nerve grafting is at the time of resection and reconstruction because a delayed approach would allow time for wallerian degeneration of the resected nerve stumps, possible trigeminal ganglion cell body death, 9 and the MILORO AND MARKIEWICZ possibility of central cortical changes that would affect the success of microneurosurgical repair. Our preliminary data have been published, 5 and the results of neurosensory recovery using VSP appear to be consistent with those results; however, additional investigation is required to determine whether an improved outcome in sensation can be observed with VSP.…”
Section: Discussionsupporting
confidence: 79%
“…This question is especially important when the current data indicate that success rates for neurosensory recovery in these cases are excellent. 4,5 In fact, these nerve ''injuries'' must be considered different from the usual third molar-related injuries to the lingual nerve or IAN, in which there is generally an avulsive injury with fascicular scarring and a time delay during which time both wallerian degeneration and central cortical changes may occur that may result in a less than ideal neurosensory recovery, although the results continue to be reported at higher levels than in the past. 6,7 These resection and immediate repair injuries are clean, controlled, sharp transection nerve injuries without prior injury, scarring, or abnormal sensations, and they are repaired with immediate microneurosurgical techniques under operating magnification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When anastomosis is performed within 14 days of nerve trauma, functional recovery is good in about 80% of patients [37]. However, with increasing time between nerve trauma and anastomosis, the extent of recovery decreases [38][39][40]. The types of changes that occur over time that lead to this decrease in recovery are discussed below.…”
Section: Restoration Of Function With Surgical Intervention-anastomosismentioning
confidence: 99%
“…4,5 However, although adequate for short gaps (<3 cm), ANAs have limited clinical data to support their use to reconstruct longer nerve gaps (>3-5 cm) to provide functional recovery, especially motor, comparable with the autograft standard. [6][7][8][9][10] In addition, multiple animal studies have demonstrated that acellular nerve scaffolds, such as ANAs, do not facilitate comparable axon regeneration to isografts 4,5 and fail to consistently facilitate axon regeneration across longer gaps (>3 cm) or promote motor recovery. 11,12 Overall, these issues present concerns regarding the use of ANAs to treat long gap clinical nerve injuries.…”
mentioning
confidence: 99%